Chronic Kidney Disease: A Comprehensive Review - Ritu; Anshika Rosha (International Journal of Emergency and Trauma Nursing and Practices, 2025)
Chronic Kidney Disease (CKD) is a progressive condition characterized by a long-term decline in kidney function, leading to a gradual deterioration of the kidneys' ability to filter waste and maintain fluid balance. It is diagnosed when the Glomerular Filtration Rate (GFR) falls below 60 ml/min/1.73 m² or when there is evidence of kidney damage (such as proteinuria) lasting for 3 months or more. The most common causes of CKD are chronic conditions such as diabetes and hypertension, which contribute to the damage of the kidney's structures over time. As the disease advances, CKD can lead to several complications that impact overall health. Anemia, often due to reduced erythropoietin production by the kidneys, and cardiovascular diseases, including hypertension and heart failure, are prevalent in CKD patients. Furthermore, if left untreated, CKD may progress to end-stage renal disease (ESRD), where kidney function becomes critically low, and the patient may require dialysis or a kidney transplant to sustain life. Early detection of CKD is essential for effective management. Routine screening for individuals at risk, such as those with diabetes, hypertension, or a family history of kidney disease, is recommended. Treatment strategies focus on controlling the underlying causes, such as blood pressure and blood sugar management, alongside lifestyle changes, including dietary modifications and weight management. Medical interventions, such as medications to manage symptoms and slow the progression of the disease, also play a key role in preserving kidney function and preventing the need for more intensive treatments like dialysis.
Keywords: Anemia; End-stage Renal Disease (ESRD); Glomerular Filtration Rate (GFR); chronic kidney disease (CKD); hypertension